Capacity Building on Islamic Household Management for Mothers of PRA Tohudan Colomadu - Maulidiyah Indira Hasmarini; Retno Faridatussalam; Siti Fatimah Nurhayati; Wisnu Sri Hertinjung; Muhammad Anas; Firliana Rizky Ramadhina; Pinkan Yulia Salwa; Isnaeni Hasna Hanisah (Abdi Psikonomi, 2025)
This community service program was implemented based on challenges faced by the PRA (Aisyiah Tohudan Branch Leadership) in Colomadu, Karanganyar, Central Java. The primary target group needed assistance in capacity building in Islamic household management. The problem faced by the partners was that mothers lacked an understanding of Islamic household management, which relates to planning, resource management, communication between family members, moral development within the household, children's education, and family financial management. The objectives of this community service activity were: 1. To help the primary target group understand Islamic household management, 2. To assist partners in planning, resource management, and communication between family members, 3. To assist partners in family financial management, and 4. To support partners in educating their children in accordance with current developments and Sharia guidelines. The methods used in this activity included focus group discussions, lectures, and mentoring. The community service outcomes achieved included draft articles for publication in the Abdipsikonomi journal, YouTube publications for the Development Economics Study Program, intellectual property rights (IPR) processes for posters and YouTube videos, and articles uploaded to the online media outlet Retizen Republika.